Analisis Kinerja Keuangan Berbasis Analisis SWOT pada Dinas Lingkungan Hidup Provinsi Jawa Timur - Nadia Fransiska Dewi; Muhammad Taufiq Hidayat (AKUNTANSI 45, 2026)
This study aims to analyze the financial performance of the East Java Provincial Environmental Agency (DLH) during the 2020–2024 period using financial ratio analysis and a SWOT analysis, strengthened through data triangulation. The financial ratio analysis includes the Regional Original Revenue (PAD) effectiveness ratio, expenditure efficiency ratio, expenditure harmony ratio, and revenue growth ratio. The results indicate that the financial performance of the East Java Provincial DLH is generally in the fairly good category, indicated by a high level of budget effectiveness. However, revenue growth tends to fluctuate, and the expenditure structure is still dominated by operational expenditures, while capital expenditures are relatively low. The SWOT analysis indicates that the DLH has strengths in the form of competent personnel and local government support, but faces weaknesses in the form of limited human resources and a low proportion of capital expenditures. Opportunities arise from increased attention to environmental issues and potential collaboration with the private sector, while threats stem from increasing environmental problems and budget fluctuations. This study recommends increasing institutional capacity, strengthening cross-sector collaboration, and restructuring spending priorities to support sustainable environmental development.